Digital Agility and Knowledge Sharing to Increase MSMEs Performance : An Empirical Study in MSMEs in Semarang City - Yuniarti, Nur Atika; Mutiarachim, Atika (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study investigates how digital agility and knowledge-sharing culture affect the performance of Micro Small and Medium Enterprises (MSMEs) in Semarang City, with innovation performance as a mediating factor. In today's rapidly evolving technological and business landscape, digital agility enables organizations and individuals to adapt swiftly, maintaining relevance and competitiveness. Knowledge-sharing culture facilitates the exchange of expertise and experiences, fostering new ideas through the combination of diverse knowledge. The research proposes seven hypotheses. First, digital agility's effect on innovation performance. Second, knowledge sharing's impact on innovation performance. Third, digital agility's influence on MSMEs performance. Fourth, knowledge sharing's effect on MSMEs performance. Fifth, innovation performance's impact on MSMEs performance. The indirect effect, digital agility has a positive and significant effect on MSMEs performance through innovation performance as a hypothesis 6, then knowledge sharing has a positive and significant effect on MSMEs performance through innovation performance as a hypothesis 7. The study surveyed 100 MSMEs owners in Semarang City, categorized by their business net income. Data analysis was conducted using SMART-PLS 4 software. Results indicate that both digital agility and knowledge sharing positively and significantly influence innovation performance. While digital agility has a positive but insignificant direct effect on MSMEs performance, knowledge sharing demonstrates a positive and significant direct impact. Importantly, the study reveals that digital agility and knowledge sharing indirectly enhance MSMEs performance through innovation performance. This research emphasizes the importance of digital agility and knowledge-sharing culture in improving MSMEs performance. As MSMEs reach critical growth stages, implementing more productive methods through digital agility and knowledge sharing becomes crucial. These practices generate new ideas, fostering creativity and innovation within the organization. The resulting innovation competitiveness allows MSMEs to develop unique products or services, creating a competitive advantage and attracting new customers.